Estimation of Reliability Based on Rayleigh Distribution - Hazaymeh, Ayman; Batiha, Anwar; Alodat, Naser; Qawasmeh, Tariq; Abdelrahim, Ra'ft; Adam Hassan, Abdelgabar; Ayser Taahat; Al-Sharqi, Faisal (Statistics, Optimization & Information Computing, 2026)
The estimation of p(x>y) where x and y are two independent Rayleigh distributions is the focus of this work. The asymptotic distribution of the maximum likelihood is obtained. Both the approximate maximum likelihood estimator of R and the maximum likelihood estimator are suggested. We derive the maximum likelihood estimate of R's asymptotic distribution. The asymptotic distribution can be used to determine the R confidence interval.